ABNORMAL PSYCHOLOGY APPEARANCE “EXECUTIONER" IN NOVEL OF IVAN FRANCO “CROSS PATHS" AND DRAMA OF VOLODYMYR VYNNYCHENKO “A SIN" - Kobzey , N. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article attention is paid to the poetic meaning of the psichopatologic characters in Franko’s and Vynnychenko’s creative work on the basis jf evolution process of social and psychologic alone.